Mid-range visual functions in relation to higher-order visual functions after stroke. Issue 8 (14th September 2022) - van den Berg, Nils S.; Lammers, Nikki A.; Smits, Anouk R.; Lugtmeijer, Selma; Pinto, Yair; De Haan, Edward H.F.
ABSTRACT: Introduction: We aimed to investigate whether associations between deficits in "mid-range" visual functions and deficits in higher-order visual cognitive functions in stroke patients are more in line with a hierarchical, two-pathway model of the visual brain, or with a patchwork model, which assumes a parallel organization with many processing routes and cross-talk. Methods: A group of 182 ischemic stroke patients was assessed with a new diagnostic set-up for the investigation of a comprehensive range of visuosensory mid-range functions: color, shape, location, orientation, correlated motion, contrast and texture. With logistic regression analyses we investigated the predictive value of these mid-range functions for deficits in visuoconstruction (Copy of the Rey-Complex Figure Test), visual emotion recognition (Ekman 60 Faces Test of the FEEST) and visual memory (computerized Doors-test). Results: Results showed that performance on most mid-range visual tasks could not predict performance on higher-order visual cognitive tasks. Correlations were low to weak. Impaired visuoconstruction and visual memory were only modestly predicted by a worse location perception. Impaired emotion perception was modestly predicted by a worse orientation perception. In addition, double dissociations were found: there were patients with selective deficits in mid-range visual functions without higher-order visual deficits and vice versa. Conclusions: Our findings are not in line with the hierarchical, two-pathway model. Instead, the findings are more in line with alternative "patchwork" models, arguing for a parallel organization with many processing routes and cross-talk. However, future studies are needed to test these alternative models.